Particularities of media systems in the West Nordic countries - Ravn-Højgaard Signe; Jóhannsdóttir Valgerður; Karlsson Ragnar; Olavson Rógvi; Skorini Heini í (Nordicom Review, 2021)
This study compares the media systems of the West Nordic countries, namely the Faroe Islands, Greenland, and Iceland. All three countries are democratic welfare states with considerable institutional transfer from the larger Nordic countries. It is argued that the West Nordic media systems fit into the “Nordic model” when it comes to the perception of media as cultural institutions as well as the central role of public service media. On the other hand, the micro-size of the media systems in the West Nordic countries makes them vulnerable, and makes editorial independence more difficult compared with their larger Nordic neighbours. In particular, media outlets within these micro-size media systems seem more susceptible to clientelism, and journalists seem more inclined towards self-censorship. This article highlights how interplay between small size and distinct local factors shape the media system in each of the West Nordic countries.